IDENTIFIKASI SUMBER BAHAYA (HAZARD) DALAM PENERAPAN KESELAMATAN DAN KESEHATAN KERJA DI INDUTRI PENGGERGAJIAN KAYU BERKAT SHALAWAT KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Vania, Desti; Sribudiani, Evi; M. Mardhiansyah, M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Protection of safety and occupational health is still far from expected because there are still many accidents and potential work hazard that many endanger the workers. Yet until now they do not have good reference on standardization of producttion process and product standardization, one of them is safety and occupational health standard (K3). The absence of such standardizationcause business owner pay less attention to environmental conditions and business facilities. Problem arise are workers tend to work without sufficient knowledge and ignore the use of personal protective equipment (PPE). These things cause workers to be susceptible on disruptions, accidents and illnesses arising from working condition. The aim of this study was to identify the hazard in the implementation of safety and health in the sawmill Berkat Shalawat Tembilahan district Indragiri Hilir regency.This research used descriptive analysis with observation method and interview with took sample of all workers in Berkat Shalawat industry. The result ofidentification indicated that the dominant danger source of accidents at the stages of loading and unloading, wood clearance and loading to the mean of transportation, those are wounds from wood fiber, pincers, crushed wood etc. In other hand, workers also experiance musculoskeletal symptoms, coughing, fatigue and decreased vision and hearing fuction that are shown in physical, chemical, biological and ergonomic factors. Keyword: Safety and Occupational Health, Hazard Source, Personal Protective Equipment (PPE).